Upaya Penanggulangan Penyalahgunaan Narkotika oleh Remaja di Jayapura dalam Perspektif Hukum Pidana - Muhammad Yusuf; Mursani Mursani; Tri Mulyadi (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
Drug abuse among adolescents in Jayapura City is a pressing issue with significant repercussions for health, society, and the future of younger generations. Due to Jayapura's strategic position as a border city with Papua New Guinea, it faces a heightened risk of cross-border drug trafficking, making it particularly vulnerable. This study explores the various factors contributing to the rise in drug abuse among adolescents, including individual, family, and peer group dynamics, socio-economic conditions, weak legal enforcement, and the influence of globalization. The findings suggest that a multifaceted approach is essential in addressing the problem. Repressive measures alone are insufficient, and should be complemented by preventive, rehabilitative, and educational strategies. Such approaches must emphasize child protection principles and ensure justice that is both substantive and forward-thinking. Progressive and responsive legal frameworks, aligned with the goals of criminal punishment, are necessary to effectively combat drug abuse in Jayapura. Moreover, these frameworks should prioritize adolescent recovery, recognizing that these individuals are the future of the nation.